The Invisible Engineers: How Viruses Change Cells at the Molecular Level - V. Basil Hans (International Journal of Virus Studies, 2026)
Viruses are frequently thought of as simple parasites, yet at the molecular level, they are quite good at engineering and may change the way the cells they infect work. The Invisible Engineers: How Viruses Rewire Cells at the Molecular Scale looks into how viruses get into host cells, mess up intracellular circuits, and exploit molecular resources to make copies of themselves. This article talks about how viral proteins and nucleic acids change gene expression, restructure organelles, and change immune responses by interacting with host machinery. It does this by using new information from structural biology, genomics, and cell imaging. By looking at these processes in different viral families, we find common rules that control how viruses change cells and the evolutionary forces that shape them. Comprehending these molecular interactions not only clarifies essential elements of cell biology but also guides the advancement of antiviral medicines and technologies derived from viral processes. This article gives a complete picture of the molecular choreography that happens during an infection. It helps readers understand viruses better as active and complex players in the cellular environment.
Keywords: Cellular reprogramming; Pathogenesis; molecular processes; structural virology; viral-host interactions